Prevalence of obesity in preschool children from five towns in São Paulo State, Brazil Prevalência de obesidade infantil em cinco municípios do Estado de São Paulo, Brasil - Silvia Regina Dias Medici Saldiva; Maria Mercedes Loureiro Escuder; Sonia Isoyama Venâncio; Maria Helena D'Aquino Benicio (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2004)
Health and nutritional characteristics of children under 5 years of age were investigated through a cross-sectional study in 5 small cities from different regions in the State of São Paulo, Brazil, which displayed different socioeconomic profiles: Bady Bassit, Bofete, Jaborandi, Morungaba, and Riversul. Data were obtained using a systematic sampling from the 1991 National Census. Anthropometric data were collected from all children under 5 years of age living in the selected households. Nutritional status was determined by height/age and weight/height according to the National Center for Health Statistics - NCHS standards. Stunting was defined as HAZ below - 2 Z scores and obesity as WHZ above 2 Z scores. The study sample consisted of 987 children (490 boys and 497 girls). Prevalence of obesity was 6.6% (65) and stunting 5.0% (51). Per capita income displayed a significant and positive association with obesity (p = 0.018), in contrast to an inverse association with stunting (p = 0.038). Com o intuito de conhecer a saúde e nutrição de crianças menores de cinco anos que residiam em municípios de pequeno porte no Estado de São Paulo, Brasil, foi realizado um inquérito domiciliar em cinco municípios: Bady Bassit, Bofete, Jaborandi, Morungaba e Riversul, localizados em diferentes regiões geográficas e com perfis distintos de desenvolvimento. A coleta de dados foi realizada por meio de sorteio sistemático dos domicílios com base no Censo Demográfico de 1991. Foram consideradas com déficit de altura crianças com o índice altura/idade menor que -2 scores Z, e para a obesidade aquelas com o índice de peso/altura maior que 2 scores Z, segundo o National Center for Health Statistics, Estados Unidos. A amostra foi composta por 987 crianças (490 meninos e 497 meninas). A prevalência de obesidade foi de 6,6% e o déficit de altura de 5,2%. Na análise das prevalências de déficit de altura e de obesidade desagregadas por categorias de renda per capita em salários mínimos, são encontradas diferenças significativas, onde a prevalência de obesidade aumenta com o aumento da renda per capita (p = 0,018), enquanto que o déficit de altura apresentou comportamento inverso (p = 0,038).